Pentostatin, cyclophosphamide and rituximab is a safe and effective treatment in patients with Waldenström’s macroglobulinemia - Krämer, Isabelle; Hensel, Manfred; Rieger, Michael; Horstmann, Kristin; Hiddemann, Wolfgang; Dreyling, Martin; Koniczek, Silvia; Witzens-Harig, Mathias; Ho, Anthony Dick (Leukemia and lymphoma, 2015)
Waldenström’s macroglobulinemia (WM) is an indolent lym phomaand is responsive to therapy regimens containing alkylating agents, purine analogs and rituximab if treatment becomes necessary. We initiated a multicenter phase II trial to determine the safety and efficacy of a regimen containing pentostatin, cyclophosphamide and rituximab (PER) in patients with WM. Between May 2005 and December 2010, 25 patients with WM were included in the study. Twenty-one patients received PER as first-line therapy. In these patients, 2-year progression-free survival was 83.6% and 2-year overall survival was 100%. Thirteen patients (52%) received R maintenance therapy. In these patients, the 2-year progression-free survival was 91.67% and 2-year overall survival was 100%. We have provided evidence that PER is a safe and effective regimen for WM. Although R maintenance therapy after PER seemed to induce a better long-term outcome, this study was not powered to address this issue.